FLA-Dataset: A Database of Four Location-Based Audio Commands in Brazilian Portuguese - Silva, Daniel Ribeiro da; Ruotolo, Gabriel Pettro Oliveira; Ferro Filho, Alexandre Costa; Ferreira, Marcelo Henrique Lopes; Mendes, Letícia Lima; Teles, José Rafael Rebêlo (Anais da Escola Regional de Informática de Goiás (ERI-GO), 2025)
The FLA-Dataset provides a curated collection of wake word audio commands in Brazilian Portuguese. It supports the development and evaluation of voice-activated systems by including four direction-oriented commands: direita, esquerda, frente, and pare. Recordings are contributed by 30 speakers across diverse demographic and acoustic profiles. The dataset promotes generalization by incorporating varied speech patterns, environments, and genders. All files are standardized in format, sampling rate, and structure to ensure usability. Each sample contains a single spoken command and is organized to allow speaker-specific experiments. Applications span robotics, assistive technologies, and smart devices. The dataset addresses the scarcity of localized resources for Portuguese. It enables speaker-independent training and evaluation in realistic scenarios. FLA-Dataset is publicly available and designed to support inclusive speech recognition research and deployment.